Dynamics of Land Inequality: Polarization or Pauperization?. Issue 2 (August 2018) - Krishnaji, N.
This paper looks at land ownership in rural India. It shows a high concentration of land in the hands of the rich at the top along with a proliferation of small holdings and a steady growth in numbers of rural labour households among whom a significant proportion own and cultivate some land. The underlying processes are analysed here using a Marxian framework, more specifically the models of Karl Kautsky and V.I. Lenin that extend the Marxian logic to agrarian structures. They note in particular that among the differentiated peasantry the small ones can survive without losing their land by several means that include the proverbial 'tightening of the belt' to reduce household consumption levels, as also to other factors such as their ability to lease in land to the extent possible and their entry into markets as sellers of the produce of commercial crops. The analysis shows a broad consistency of the Indian data with the Kautsky and Lenin models. It is seen that, apart from this, the state has played a major role – one that is a necessary part of populist politics – in supporting the small peasantry.